PERANCANGAN DAN ANALISIS PEMBEBANAN GERGAJI RADIAL 4 ARAH - Michael Wijaya Wijaya; Didi Widya Utama; Agus Halim (Jurnal Ilmiah Teknik Mesin POROS, 2017)
Abstract: 4 ways hacksaw is one type of wood hacksaw, which has 4 arms wood hacksaw and connected by linkage, so that can make translation movement. This 4 ways hacksaw powered by 1,5 HP AC Motor. This 4 ways hacksaw design, performed modeling and construction load simulation was made and simulated by Autodesk Inventor Professional 2014 software. And also on this load simulation this product also had good strength and ability to receive the maximum load force. So it is safe to be use